Implementasi Etika Foto Jurnalistik Berita Hukum dan Kriminal pada Media Jambiupdate.co - Asmarita Sari; Sururuddin; Usrial Husein; Agus Slamet Nugroho (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research is motivated by the problem of photojournalism that is not in accordance with the rules contained in the Journalistic Code of Ethics. The aim of this research is to find out how the Code of Ethics is applied to the Legal and Criminal News Photo in Jambiupdate.co itself. The research method used is qualitative with data analysis using Charles Sanders Peirce semiotics. The results of the study show that in general there are journalists who are not in accordance with the Code of Ethics. Likewise with the Journalistic Code of Ethics which regulates the ethics of journalists and the media in broadcasting photos in a news story. Jambiupdate.co online media, like other online media, will certainly try to apply the Photojournalism Code of Ethics in every news story, but the implementation is certainly not as easy as expected, because it is the principle of news speed which sometimes does not pay attention to the Code of Ethics itself and the lack of communication between journalists in the field. with the editorial team. In addition, violations of the photojournalism code of ethics are negligence or forgetting to blur photos that contain sadistic elements and the victim or perpetrator is a woman and a minor who is protected by the photojournalism code of ethics law.